2022
DOI: 10.3390/ijms232113328
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Immunity and the Gut-Microbiota-Brain-Axis in Neuroimmune Disease

Abstract: Recent advances in next-generation sequencing (NGS) technologies have opened the door to a wellspring of information regarding the composition of the gut microbiota. Leveraging NGS technology, early metagenomic studies revealed that several diseases, such as Alzheimer’s disease, Parkinson’s disease, autism, and myalgic encephalomyelitis, are characterized by alterations in the diversity of gut-associated microbes. More recently, interest has shifted toward understanding how these microbes impact their host, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 340 publications
0
2
0
Order By: Relevance
“…The Fc receptor CD16a (FcγRIIIa), a feature of CD56Dim NK cells, interacts with the constant region of Immunoglobulin G (IgG) antibodies. This interaction triggers Antibody-Dependent Cell-Mediated Cytotoxicity, a process that is crucial for the NK cells' ability to eliminate target cells[ 50 ]. In the gastrointestinal tract, NK cells may exert a more pronounced influence on gut homeostasis compared to their circulating counterparts, owing to their localized cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…The Fc receptor CD16a (FcγRIIIa), a feature of CD56Dim NK cells, interacts with the constant region of Immunoglobulin G (IgG) antibodies. This interaction triggers Antibody-Dependent Cell-Mediated Cytotoxicity, a process that is crucial for the NK cells' ability to eliminate target cells[ 50 ]. In the gastrointestinal tract, NK cells may exert a more pronounced influence on gut homeostasis compared to their circulating counterparts, owing to their localized cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The gut microbiota and its metabolites play a crucial role in the metabolism of neurotransmitters, which are key participants in neuroimmunity. 12 Imbalance between excitatory and inhibitory neurotransmitters in the nervous system is associated with the development and progression of neurological diseases. 13 In recent years, there has been increasing interest in exploring the potential effects of periodontitis outside the oral cavity, particularly its impact on the nervous system.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Some studies have shown that the gut microbiota communicates bidirectionally with the nervous system through regulating neurologic and immune‐related signaling pathways, participating in the development and progression of various neurological diseases 10,11 . The gut microbiota and its metabolites play a crucial role in the metabolism of neurotransmitters, which are key participants in neuroimmunity 12 . Imbalance between excitatory and inhibitory neurotransmitters in the nervous system is associated with the development and progression of neurological diseases 13 …”
Section: Introductionmentioning
confidence: 99%
“…Among the NDs, a research study has shown that in AD brain, microglial activation contributes to amyloid-beta deposition and neuronal damage [41]. In addition, in PD few research studies have shown that in the brain T cells infiltrate the substantia nigra and promote neuroinflammation [42,43]. Moreover, in multiple sclerosis, few studies have shown that dysbiosis and gut-derived molecules contribute to neuroinflammation and disease progression [44][45][46].…”
Section: Critical Network Of Bacterial Extracellular Vesicles In the ...mentioning
confidence: 99%
“…This neuroimmune system helps keep the homeostasis in balance. If this balance is distraught, it can lead to chronic inflammation, damage to neurons, and eventually NDs [41,42]. In terms of NDs, the neuroimmune system is made up of immune cells like microglia and astrocytes that become active when there is neuroinflammation [43].…”
Section: Role Of Bacterial Extracellular Vesicles In Neuroimmune Syst...mentioning
confidence: 99%